اتجاهات البراعم نحو مراكز اللعب في كرة القدم بولاية الخرطوم - محمود، عوض يس أحمد; حاج إبراهيم، الطيب (جامعة محمد بوضياف المسيلة - معهد علوم وتقنيات النشاطات البدنية والرياضية, 2016)
هدفت الدراسة إلى التعرف على اتجاهات البراعم نحو مراكز كرة القدم بولاية الخرطوم. استخدم الباحث المنهج الوصفي، وكانت العينة عشوائية لبراعم كرة القدم وعددهم 418. واستخدم الباحث الاستبانة كوسيلة جمع البيانات، أهم النتائج: أسفرت الدراسة أن معظم اتجاهات البراعم كانت تجاه مركز الوسط يليه مركز الدفاع ثم يليه مركز الهجوم وأخيرا مركز حراسة المرمى، أهم التوصيات: ترغيب البراعم للاتجاه للمراكز الأضعف اتجاها ورغبة خاصة مركزي الهجوم وحراسة المرمى - الدور الكبير لمراكز التدريب والمدربين في صقل المواهب وتشجيعها والمساعدة ببرامج التدريب لتوجيه البراعم نحو مراكز اللعب.
The study aimed at identifying where junior footballers head to in terms of playing positions in Khartoum state. The descriptive methodology was used. The study sample was a random selection from the junior footballers and they were 418. The tools of data collection were questionnaires. Important results were that most junior footballers head towards the center position, then the defense position, followed by the attack position and finally the goalkeeper position. Important recommendations: encouraging the junior footballers to head to the least wanted positions, namely the attack and the goalkeeper positions. Recognizing the huge role impacted by the training centers and the trainers in order to polish the raw talent and encouraging them, and also help them by the training programs, so that junior players head toward the playing centers.
Keywords: كرة القدم -- ولاية الخرطوم (السودان) -- التدريب الرياضي